2020
DOI: 10.1002/ird.2399
|View full text |Cite
|
Sign up to set email alerts
|

SPATIO‐TEMPORAL VARIATIONS OF SEVEN WEATHER VARIABLES IN IRAN: APPLICATION OF CRU TS AND GPCC DATA SETS

Abstract: Iran's climate‐sensitive agriculture and water resources are vulnerable to climate change and investigation of climatic trends helps in preparing adaptation strategies. Weather stations are sparsely distributed and access to complete weather data is limited. In such situations, gridded global/regional data sets are promising alternatives. Here, monthly time series of seven weather variables (i.e. monthly averages or monthly totals of daily values) were obtained from the Climatic Research Unit TS V4.01 and Glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…PET is evaluated using a version of Penman‐Monteith equation (FAO, 2020), which considers max temperature, minimum temperature, vapour pressure, cloud cover and wind velocity as inputs (Harris et al, 2014). This dataset has been pervasively used in recent literature (Ababaei, 2020; Sinha et al, 2018). Further, gridded datasets are spatially averaged at a catchment scale (lumped approach) to obtain the precipitation data and potential evapotranspiration data for respective catchment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PET is evaluated using a version of Penman‐Monteith equation (FAO, 2020), which considers max temperature, minimum temperature, vapour pressure, cloud cover and wind velocity as inputs (Harris et al, 2014). This dataset has been pervasively used in recent literature (Ababaei, 2020; Sinha et al, 2018). Further, gridded datasets are spatially averaged at a catchment scale (lumped approach) to obtain the precipitation data and potential evapotranspiration data for respective catchment.…”
Section: Methodsmentioning
confidence: 99%
“…This dataset has been pervasively used in recent literature (Ababaei, 2020;Sinha et al, 2018). Further, gridded datasets are spatially averaged at a catchment scale (lumped approach) to obtain the precipitation data and potential evapotranspiration data for respective catchment.…”
Section: Datasetsmentioning
confidence: 99%
“…The test has been frequently adopted in hydrological and meteorological studies (e.g. Tabari and Hosseinzadeh Talaee, 2011;Gocic and Trajkovic, 2013;Khalili et al, 2016;Araghi et al, 2018;Ababaei and Chenu, 2019;Ababaei and Ramezani Etedali, 2019;Ababaei, 2020;Alizadeh et al, 2020) and its calculation procedure can be found in Ababaei and Chenu (2020). The accuracy of the test is affected by the presence of serial correlation.…”
Section: Temporal Trend Analysismentioning
confidence: 99%
“…Great many climate risk studies have analysed the univariate hydroclimatic extremes. It has been shown that heatwave magnitudes, frequencies, intensities, and spatial extents are increasing in Australia (Ababaei and Chenu, 2020) and other regions of the world (Pai et al, 2013;Cheng et al, 2014;Sun et al, 2014;Christidis et al, 2015;Ramezani Etedali et al, 2018;Ababaei and Ramezani Etedali, 2019;Ababaei, 2020), a trend that is projected to continue in a warming climate (Lobell et al, 2015;Murari et al, 2015;Alexander and Arblaster, 2017;Zscheischler et al, 2018;Trancoso et al, 2020). Moreover, analyses of historical precipitation, streamflow, and soil moisture indices show an increasing trend of aridity over many regions across the world (Hennessy et al, 1999;Vicente-Serrano et al, 2010;Wang et al, 2011;Mishra and Liu, 2014;Mallya et al, 2015;Araghi et al, 2018;Ababaei and Ramezani Etedali, 2019;Ababaei, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation